Application of Heat Transfer for Designing Landscapes to Reduce Air Temperature in Buildings - Chanchit, Kumjan; Maksuwan, Atirat (Journal of Vocational Education in Agriculture, 2024)
The objective of this research was to compare the rate of air temperature reduction per unit time from designing landscapes to reducing air temperature in buildings. The research methodology was divided into four steps. The first step is to select plants, including large, medium, and small shrubs and ground-covered plants. According to the criteria for evaluating the potential properties for use in landscape applications. The second step is to landscape design by creating perspective images, that is, sketching images in a way that looks like real vision from arranging plants that have been selected in different directions and sizes. The third step is to calculate the thermal conductivity of plants and ground cover and finally, application of heat transfer to create a curve for the decreasing rate of air temperature change per unit time. The results of this research show that landscaping designs that maximize the area of large shrubs and are positioned in front of buildings have the greatest trend lines in the rate of temperature change per unit time.